Content Analysis through TikTok Social Media Comments: Use of Herbal Medicine - Oktaviana, Felicia; Hastjarjo, Sri; Rahmanto, Andre (PT FORMOSA CENDEKIA GLOBAL, 2024)
Obesity is a condition where there is excessive accumulation of body fat so that a person's weight is far above normal, this is caused by an imbalance in energy intake and expenditure. The high number of Tiktok users in Indonesia makes Tiktok an effective social media application. This makes the content on Tiktok easily attract the attention of viewers in the field of health and healthy lifestyles in the comments column. This study wants to find out how the audience receives messages from health content creator Dr. Rianti Maharani with the account name @dr.riantiherbal through the comments column. This study uses a qualitative descriptive method with reception analysis theory. The subjects in this study were 17-45 years old, were viewers and provided comments on the @drriantiherbal account. The results of the study found that opposite comments appeared a lot in the comments column, namely 41 comment samples.